Genomic characterization of chronic lymphocytic leukemia in patients of African ancestry - Cecilia Bonolo de Campos; Chantal E. McCabe; Laura A. Bruins; Daniel R. O’Brien; Sochilt Brown; Renee C. Tschumper; Cristine Allmer; Yuan Xiao Zhu; Kari G. Rabe; Sameer A. Parikh; Neil E. Kay; Huihuang Yan; et al. (Blood Cancer Journal)
Abstract Despite the considerable effort to characterize the genomic landscape of chronic lymphocytic leukemia (CLL), published data have been almost exclusively derived from patients of European Ancestry (EA), with significant underrepresentation of minorities, including patients of African Ancestry (AA). To begin to address this gap, we evaluated whether differences exist in the genetic and transcriptomic features of 157 AA and 440 EA individuals diagnosed with CLL. We sequenced 59 putative driver genes and found an increased frequency of high-impact mutations in AA CLL, including genes of the DNA damage repair (DDR) pathway. Telomere erosion was also increased in AA CLL, amplifying the notion of increased genomic instability in AA CLL. Furthermore, we found transcription enrichment of the Tumor Necrosis Factor-alpha (TNFα) Signaling via NF-κB pathway in AA CLL compared to EA CLL, suggesting that tumor promoting inflammation plays an important role in AA CLL. In summary, these results suggest that genomic instability and NF-kB activation is more prevalent in AA CLL than EA CLL.